Hubungan Konsumsi Sugar Sweetened Beverages (SSB) dengan Nutrient Density pada Siswa SMA di Surakarta - Nasva Fadila Eltari Putri; Dyah Intan Puspitasari; Endang Nur Widiyaningsih (INSOLOGI: Jurnal Sains dan Teknologi, 2026)
Consumption of sugar-sweetened beverages (SSBs) among adolescents is increasing and has the potential to affect the quality of nutritional intake. This study aims to determine the relationship between SSB consumption habits and nutrient density values among public high school students in the city of Surakarta. This study is an observational analytical study with a cross-sectional design. The sample size in this study was 274 students selected using simple random sampling. Primary data were collected using a Food Frequency Questionnaire (FFQ) to describe SSB consumption frequency during the past month. Data were also obtained through a 24-hour food recall interview method over three non-consecutive days, consisting of two school days and one weekend day, to describe the respondents' daily food intake. Nutritional intake data were analyzed using NutriSurvey software and the Indonesian Food Consumption Table (TKPI), then used to calculate nutrient density values using the Nutrient Rich Food Index (NRF 9.3) method. Data analysis was performed univariately to describe the distribution of research variables and bivariately using the Spearman's rank correlation test. The results showed that there was a significant relationship between SSB consumption and nutrient density (p = 0.012) with a correlation coefficient of p = -0.151, indicating a very weak relationship. These findings indicate that increased SSB consumption tends to be associated with a decline in the quality of dietary intake among adolescents. Therefore, nutrition education and increased awareness in choosing healthier beverages are needed to support improvements in the quality of nutritional intake among adolescents.